تسيير المخاطر المصرفية في مؤسسات الخدمات المالية الإسلامية وفق مقررات Ifsb - بن عمر, محمد البشير; طيبي, عبد الطيف (جامعة الوادي - University of Eloued, 2021)
إن المخاطر التي تواجه أي عمل تكون في الأساس مرتبطة بطبيعة هذا العمل، والعمل المصرفي الإسلامي يتميز بطبيعته المختلفـة عن العمل المصرفي التقليدي، حيث يمثل النشاط الاستثماري لب وجوهر هذه الطبيعة وعمودها الفقري الذي يتوقف عليه وجود البنك من عدمـه، وبطبيعته وآليته ومنهجية عمله المختلفة عن آلية ومنهجية نظام القرض المعتمدة في البنوك التقليدية من ناحية، إضافة إلى العلاقة الحاكمة للمتعاملين مع كلا المصرفين من خلال هذين النشاطين المختلفين من حيث طبيعتهما وأساليبهما وأحكامها؛ وبطبيعة اختلاف النشاط الاستثماري وطبيعة العلاقة الحاكمة لمتعامليه بالبنك الإسلامي يؤدي إلى تمايز المخاطر التي يمكن أن يتعرض لها العمل المصرفي الإسلامي عن العمل المصرفي التقليدي؛ وعلى ضوء هذا جاءت فكرة هذا المقال حول دراسة وتحليل طبيعة المخاطر في العمل المصرفي الإسلامي وآليات تسيرها وفق ما هو مقرر من مجلس الخدمات المالية الإسلامية The risks facing any business are basically related to the nature of this business, and Islamic banking is characterized by its different nature from traditional banking, where in vestmentactivityrepresents the core and essence of this nature and its backb one up on which the existence of the bank depends or not, and its nature, mechanism and methodology of work is different from the mechanism The methodology of the loan system adopted in conventional banks on the one hand, in addition to the governing relation ship of customers with both banks through thesetwo differentactivities in terms of their nature, methods and provisions; The nature of the different investment activity and the nature of the relation ship governingits clients with the Islamicbank leads to differentiation of the risks that Islamic bankingcan be exposed to from the traditional banking business. In light of this, the idea of this article came about studying and analyzing the nature of risks in Islamic banking and the mechanisms for conducting them according to what is decided by the Islamic Financial Services Board.
Managing banking risks in Islamic financial services institutions in accordance with IFSB decisions
مقال
Keywords: المخاطر الائتمانية، سعر الصرف، مخاطر السيولة، مخاطر السوق، المخاطر الاستثنائية، متطلبات كفاية رأس المال.; credit risk, exchange rate, liquidity risk, market risk, exceptional risk, capital adequacy requirements.